2015
DOI: 10.3892/ijo.2015.3009
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells enhance cancer cell proliferation via IL-6 secretion and activation of ERK1/2

Abstract: Human mesenchymal stem cells (hMSC) are frequently used in tissue engineering. Due to their strong tumor tropism, hMSC seem to be a promising vehicle for anticancer drugs. However, interactions between hMSC and cancer are ambiguous. Particularly the cytokines and growth factors seem to play an important role in cancer progression and metastasis. The present study evaluated the effects of hMSC on head and neck squamous cell carcinoma (HNSCC) cell lines (FaDu and HLaC78) in vitro. hMSC released several cytokines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 43 publications
3
29
1
Order By: Relevance
“…IL-6 and IL-8 are chemotactic cytokines and mediators of stem cell activation [54]. Furthermore, MSCs promote tumor cell progression via IL-6 secretion and proangiogenic factors [55]. In contrast to the present study, other metal oxide nanoparticles, such as silver oxide NPs [32] and zinc oxide NPs [56], lead to the increased secretion of those cytokines.…”
Section: Discussioncontrasting
confidence: 80%
“…IL-6 and IL-8 are chemotactic cytokines and mediators of stem cell activation [54]. Furthermore, MSCs promote tumor cell progression via IL-6 secretion and proangiogenic factors [55]. In contrast to the present study, other metal oxide nanoparticles, such as silver oxide NPs [32] and zinc oxide NPs [56], lead to the increased secretion of those cytokines.…”
Section: Discussioncontrasting
confidence: 80%
“…Both TNF‐ and TNF/IL‐6–treated BMMs expressed markers of osteoclast differentiation (Figure C), but only the latter formed multinucleated osteoclasts (Figures A and B and Figures C and D). Removing IL‐6 on day 2 of culture reduced, but did not eliminate, RANKL‐independent osteoclastogenesis (Supplementary Figure 3A, available at http://onlinelibrary.wiley.com/doi/10.1002/art.39837/abstract), suggesting that IL‐6 may have pro‐proliferative effects on precursors . Indeed, RANKL and TNF inhibited proliferation compared to M‐CSF alone, while IL‐6 promoted proliferation in the presence of TNF to levels similar to those of M‐CSF alone (Supplementary Figure 3B).…”
Section: Resultsmentioning
confidence: 97%
“…Activation of ERK1/2 by MSC-CM was also reported by Scherzad et al . They showed that proliferation of head and neck squamous cell lines cultured in MSC-CM was induced by soluble mediators secreted by MSCs, mainly IL-6 56 .…”
Section: Discussionmentioning
confidence: 99%